2013
DOI: 10.1016/j.molcel.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Degron Recognition by APC/C Coactivators from the Structure of an Acm1-Cdh1 Complex

Abstract: SummaryThe anaphase-promoting complex/cyclosome (APC/C) regulates sister chromatid segregation and the exit from mitosis. Selection of most APC/C substrates is controlled by coactivator subunits (either Cdc20 or Cdh1) that interact with substrate destruction motifs—predominantly the destruction (D) box and KEN box degrons. How coactivators recognize D box degrons and how this is inhibited by APC/C regulatory proteins is not defined at the atomic level. Here, from the crystal structure of S. cerevisiae Cdh1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
242
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(247 citation statements)
references
References 59 publications
5
242
0
Order By: Relevance
“…In addition, genetic ablation of CDC20 results in complete tumour regression in mice in comparison with treatment with taxol, vincristine or BI2536, which only induces partial responses 37 . Although CDH1 is known to target for degradation, a wide range of mitotic proteins including motor kinesins, kinases and CDC20 itself 8,24 , in our knowledge there is no mitotic phenotype associated with APC/C-CDH1 inhibition. However, inhibition of APC/C-CDH1 is suggested to impair DNA damage response to genotoxic stress 38 , shorten G1 and prolong S phase 39 , induce replicative stress 40 and impair cell motility by reducing stress fibre formation 41 .…”
Section: Ub-eg5mentioning
confidence: 94%
“…In addition, genetic ablation of CDC20 results in complete tumour regression in mice in comparison with treatment with taxol, vincristine or BI2536, which only induces partial responses 37 . Although CDH1 is known to target for degradation, a wide range of mitotic proteins including motor kinesins, kinases and CDC20 itself 8,24 , in our knowledge there is no mitotic phenotype associated with APC/C-CDH1 inhibition. However, inhibition of APC/C-CDH1 is suggested to impair DNA damage response to genotoxic stress 38 , shorten G1 and prolong S phase 39 , induce replicative stress 40 and impair cell motility by reducing stress fibre formation 41 .…”
Section: Ub-eg5mentioning
confidence: 94%
“…Structural studies of Cdc20 and Cdh1 have revealed similar APC/C degron-binding surfaces in these activators (15)(16)(17). They each contain a single, highly conserved KEN box-binding site on the top face of the ␤ propeller formed by their WD40 domain and a D box-binding site at the side of the ␤ propeller (Fig.…”
Section: Human Bubr1mmentioning
confidence: 99%
“…APC/C substrates are recognized through multiple, short degradation motifs called degrons, such as the destruction box (D box) and the KEN box (8). The KEN box is recognized by Cdc20 or its homolog Cdh1 (15)(16)(17), whereas the D box binds at the interface between Cdc20 (or Cdh1) and the core APC/C subunit APC10 (18,19). The MCC component BubR1 (or its yeast ortholog Mad3) contains two KEN boxes, which are required for checkpoint function and compete with KEN box-containing substrates for Cdc20 binding (20 -23).…”
mentioning
confidence: 99%
“…The destruction box (D-box) was the first APC/C degron identified (Glotzer et al 1991), and this 10-amino-acid motif binds to a bipartite receptor composed of the APC10 subunit and a second coactivator protein, Cdc20 (Passmore et al 2003;Passmore and Barford 2005;Matyskiela and Morgan 2009;Buschhorn et al 2011;da Fonseca et al 2011;Izawa and Pines 2011;He et al 2013). Cdc20 is replaced by Cdh1 later in mitosis in somatic cell cycles.…”
Section: Sister Chromatid Separationmentioning
confidence: 99%
“…Cdc20 and Cdh1 bind reversibly to the APC/C and, in doing so, activate it by changing its conformation to reposition APC11 to recruit the E2 enzyme in closer proximity to the bound substrate (Chang et al 2014). Cdc20 and Cdh1 are WD40 family members and the aminoterminal residues of the D-box bind between blades 1 and 7 of the WD40 domain; the carboxy-terminal residues bind to APC10 (He et al 2013). A second degron, Lys-Glu-Asn, called the KEN-box, binds to the top surface of the WD40 domain (Kraft et al 2005;Buschhorn et al 2011;Chao et al 2012).…”
Section: Sister Chromatid Separationmentioning
confidence: 99%